Proceedings of the 4th Conference on Gender &Amp; IT - GenderIT '18 2018
DOI: 10.1145/3196839.3196867
|View full text |Cite
|
Sign up to set email alerts
|

Programming in secondary schools in Norway

Abstract: This paper discusses a pilot introducing programming as an elective in Norwegian secondary schools. Computing is a male dominated field, in Norway as in other European and Western countries. Despite the male dominance in the field, there were no gender inclusion or diversity measures included in the pilot. The result is an elective heavily dominated by boys and a wasted chance of attracting girls to computing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Despite gendered patterns in education, gender remains a little discussed issue in Norwegian schools (Mathiesen et al, 2010), including in questions relating to girls' (lack of) participation in ICT subjects (Corneliussen and Tveranger, 2018). Gender stereotypes combined with young people's lack of knowledge about ICT disciplines also have a more negative effect on girls than boys, making it less likely for girls to move from high school to higher ICT education (Talks et al, 2019).…”
Section: Women's Entry Points Into Ict Education and Work: A Literatu...mentioning
confidence: 99%
“…Despite gendered patterns in education, gender remains a little discussed issue in Norwegian schools (Mathiesen et al, 2010), including in questions relating to girls' (lack of) participation in ICT subjects (Corneliussen and Tveranger, 2018). Gender stereotypes combined with young people's lack of knowledge about ICT disciplines also have a more negative effect on girls than boys, making it less likely for girls to move from high school to higher ICT education (Talks et al, 2019).…”
Section: Women's Entry Points Into Ict Education and Work: A Literatu...mentioning
confidence: 99%
“…Despite gendered patterns in education, gender remains a little discussed issue in Norwegian schools (Mathiesen et al, 2010), including in questions relating to girls' (lack of) participation in ICT subjects (Corneliussen and Tveranger, 2018). Gender stereotypes combined with young people's lack of knowledge about ICT disciplines also have a more negative effect on girls than boys, making it less likely for girls to move from high school to higher ICT education (Talks et al, 2019).…”
Section: Women's Entry Points Into Ict Education and Work: A Literatu...mentioning
confidence: 99%
“…This is the cultural context of the national project introducing programming in secondary schools in Norway, as a pilot running between 2016 and 2019. The pilot material contains a "trial curriculum", not very detailed, and with nothing about gender or inclusion [11]. A survey of the 140 pilot schools spread across the country showed that a total of 18% girls participated the first year, however only 15% the second year of the pilot.…”
Section: Introductionmentioning
confidence: 99%